Distributed load shedding for microgrid with compensation support via wireless network. Issue 9 (7th March 2018) - Xu, Qimin; Yang, Bo; Chen, Cailian; Lin, Feilong; Guan, Xinping
Abstract : Due to the limited generation and finite inertia, microgrids suffer from a large frequency and voltage deviation which can lead to system collapse. Thus, a reliable load shedding method is required to maintain frequency stability. A wireless network, benefiting from the high flexibility and low deployment cost, is considered as a promising technology for fine‐grained management. In this study, a distributed load shedding solution via a wireless network is proposed for balancing the supply–demand and reducing the load‐shedding amount. Firstly, the real‐power coordination of different priority loads is formulated as an optimisation problem. To solve this problem, a distributed load shedding algorithm based on sub‐gradient method is developed for gradually shedding loads. Using this method, power compensation can be utilised and has more time to decrease the power deficit, consequently reducing the load‐shedding amount. Secondly, a multicast metropolis schedule based on time‐division multiple access is developed. In this protocol, time slots are dedicatedly allocated to increase the response rate. A checking and retransmission mechanism is utilised to enhance the reliability of our method. Finally, the proposed solution is evaluated by using an NS3‐Matlab co‐simulator. The numerical results demonstrate the feasibility and effectiveness of our solution.